From family conflicts to suicide risk through deliberate self-harm online content in adolescents and young adults - Fuschini, Beatriz (2024)
self-harm (DSH) and even suicidal thoughts and behaviors. Research also shows that adolescents are increasingly engaging in online DSH activities. However, studies on this topic are scarce. Aims: This study’s first goal is to replicate the effect of family conflicts on suicidal ideation (SI) and, according to the gateway theory, include DSH diversity as a step preceding SI. Second, we aim to consider online activities in understanding suicidal risk. We start by describing online DSH activities, and propose a sequential mediation model in which family conflicts predict DSH and SI through online DSH activities. Methods: The convenience sample of this cross-sectional study consisted of 357 adolescents and young adults between 12 and 22 years old who completed a self-report questionnaire measuring family conflicts, online DSH activities, identification with DSH-related content creators, DSH, and suicidal ideation. Results: The results showed that 85.3% of our community sample used the internet for DSH-related purposes. Results also revealed an independent mediation effect of DSH diversity on the relationship between family conflicts and SI, and a sequential mediation effect of online DSH activities, identification, and DSH diversity. Conclusions: Engaging in online DSH activities is only predictive of DSH or SI if adolescents perceive a shared identity with this community of creators. The findings might yield implications regarding the design of prevention strategies that include a further supervision of online platforms and psychological interventions that incorporate the family system and peers